IGF axis and other factors in HPV-related and HPV-unrelated carcinogenesis (Review) - DURZYŃSKA, JULIA (Oncol Rep, 2014)
The insulin-like growth factor (IGF) axis promotes the growth of cells, tissues and organs. IGF-1 is mainly produced in the liver but is also secreted from local tissues. In the circulation, IGF-1 is bound to insulin-like binding proteins (IGFBPs), and when released it activates the insulin-like growth factor receptor (IGF-1R). The signal is further transmitted by intracellular signaling pathways leading to gene expression that regulates, among others, cell proliferation and survival. This review presents the IGF axis in the context of cell transformation and cancer development. Aspects involving IGF-1 deficiency and protection from cancer are also briefly described. Furthermore, human papillomaviruses (HPVs) interplaying with IGF axis components in cervical cancer development are described. These small dsDNA viruses are divided into low-risk and high-risk HPVs with regard to the potency of their oncogenic actions; they mainly infect epithelial or mucosal cells. Special attention is drawn to expression of two major HPV oncogenes (E6 and E7) initiating and maintaining cervical carcinogenesis, which is a multistep and multifactorial process; therefore, involvement of additional factors such as mitochondrial DNA changes, sex hormones, retinoic and folic acids are also discussed. Finally, IGF axis components and HPV oncogenes as targets in anticancer treatment are presented which include IGF-1R downregulation, RNA interference and anti-HPV therapeutic vaccines. The review concludes that despite an enormous advancement in research on IGF and HPV-related cancers, more molecular studies and clinical trials are needed before commercialized therapies are widely available for oncology patients.